The Role of Weekly One-on-One Meetings for Health Workers in Improving Patient Services in Quality Management - Elnardy, Mohammad Caesario; Lestari, Septi Intan; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (IJBLE Scientific Publications Community Inc., 2024)
Improving the quality of health services with weekly one-on-one meetings with health workers can improve the quality of health services. This research used a quantitative approach with an experimental design, involving all Medical Advisors as samples. Data is collected through valid and reliable instruments that measure the quality of One-on-one meeting. The research results showed a significant increase in service quality management after one-on-one meetings held. The average service quality score increased from 16.50 before and 43 after the intervention. There is a relationship between one-on-one meetings and improving the quality of health services. The coefficient of determination is 0.79, meaning that 79% of the variation in improving service quality is influenced by the One-on-one variable. Conclusion: Weekly one-on-one meetings are effective in improving service quality management at Klinik Lelaki Indonesia, so it is recommended to be adopted as a strategy to continuously improving service quality.